1994
DOI: 10.1128/aac.38.3.547
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe pneumonia in hospitalized patients: results of a multicenter, randomized, double-blind trial comparing intravenous ciprofloxacin with imipenem-cilastatin. The Severe Pneumonia Study Group

Abstract: Intravenously administered ciprofloxacin was compared with imipenem for the treatment of severe pneumonia. In this prospective, randomized, double-blind, multicenter trial, which included an intent-to-treat analysis, a total of 405 patients with severe pneumonia were enrolled. The mean APACHE II score was 17.6, 79%o of the patients required mechanical ventilation, and 78% had nosocomial pneumonia. A subgroup of 205 patients (98 ciprofloxacin-treated patients and 107 imipenem-treated patients) were evaluable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
251
3
18

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(286 citation statements)
references
References 50 publications
14
251
3
18
Order By: Relevance
“…From these, 51 RCTs did not meet the inclusion criteria of the current meta-analysis for the reasons detailed in figure 1. Thus, 12 RCTs [64][65][66][67][68][69][70][71][72][73][74][75] were included in the current meta-analysis. Table 1 lists the characteristics of the 12 RCTs [64][65][66][67][68][69][70][71][72][73][74][75] included in the meta-analysis.…”
Section: Data Analysis and Statistical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From these, 51 RCTs did not meet the inclusion criteria of the current meta-analysis for the reasons detailed in figure 1. Thus, 12 RCTs [64][65][66][67][68][69][70][71][72][73][74][75] were included in the current meta-analysis. Table 1 lists the characteristics of the 12 RCTs [64][65][66][67][68][69][70][71][72][73][74][75] included in the meta-analysis.…”
Section: Data Analysis and Statistical Methodsmentioning
confidence: 99%
“…The mean (range) quality score of the included RCTs was 2.42 (1-5), which was considered good. The quality of five RCTs [64][65][66][67]74] was high (o3), while the quality of seven [68][69][70][71][72][73]75] was low (f2). The proportion of patients under mechanical ventilation was 100% in three trials [67,68,71], .70% in five trials [64-66, 72, 74] and 50% in two RCTs [69,75], while the remaining RCTs [70,73] did not provide relevant data.…”
Section: Data Analysis and Statistical Methodsmentioning
confidence: 99%
“…Complicating the empiric selection of adequate therapy is the increasing prevalence of antimicrobial drug resistance among P. aeruginosa (8)(9)(10). Even in initially susceptible strains, resistance can rapidly develop during treatment (11)(12)(13).…”
mentioning
confidence: 99%
“…It was concluded that combination therapy using a fourth-generation cephalosporin with either an aminoglycoside or a fluoroquinolone was not associated with a clinical or biological benefit when compared with cephalosporin monotherapy for common, susceptible pathogens causing VAP [5]. Of the many comparative studies for the treatment of VAP, six are summarised in table 2 [6][7][8][9][10][11]. Perhaps the best of these studies compared imipenem alone with the combination of imipenem and netilmicin [8].…”
Section: Monotherapy Versus Combination Therapy: Comparisons Of Efficacymentioning
confidence: 99%